INTERNALISASI AGILE ORGANIZATIONS DALAM PENYEDERHANAAN ESELONISASI UNTUK MENINGKATKAN KINERJA PEMERINTAHAN DI INSTITUT PEMERINTAHAN DALAM NEGERI KEMENTERIAN DALAM NEGERI - Pitono, Andi; Kartiwi, Kartiwi; Baidhowah, Adfin Rochmad (Jurnal Politik Pemerintahan Dharma Praja, 2021)
growing in Indonesia. Strategic steps for the possibility of internalizing the values ​​of the five trademarks of agile organizations in downsizing bureaucracy to improve government performance at the Institut Pemerintahan Dalam Negeri can be carried out, through mapping the Institut Pemerintahan Dalam Negeri organizational structure containing echelon 3 and echelon 4 positions, changing the organizational structure of IPDN which is simplified, implementing economic incentives and job appraisal requirements, implementing one data, conducting job analysis, workload analysis, and job mapping, implementing flexible financial and human resource management, and preparing for a transition period.